2018
DOI: 10.1016/j.sjbs.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of some monofloral honey types produced across Turkey

Abstract: This study was conducted with the aim of determining the chemical, biochemical properties, and antimicrobial capabilities of some of the monofloral honeys produced in Turkey. In this study, 23 different monofloral honey samples were obtained from diverse geographical regions of Turkey. Floral origin of the honey samples was determined by melissopalinological analyses. Additionally, antioxidant properties were determined. To determine the antioxidant properties of honey samples, four test methods of total pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
4
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 62 publications
(100 reference statements)
13
89
4
5
Order By: Relevance
“…TPC in fresh AC (Table ) was significantly ( P < 0.05) higher than in fresh H. The TPC value obtained in H was in an agreement with the literature data for different honeys: 320–1190 mg kg −1 , 340–4700 mg kg −1 , or 560–2460 mg kg −1 . Also, the values presented in the literature for AC, around 1300–1500 mg kg −1 , are very close to the level determined in this study.…”
Section: Resluts and Discussionsupporting
confidence: 91%
“…TPC in fresh AC (Table ) was significantly ( P < 0.05) higher than in fresh H. The TPC value obtained in H was in an agreement with the literature data for different honeys: 320–1190 mg kg −1 , 340–4700 mg kg −1 , or 560–2460 mg kg −1 . Also, the values presented in the literature for AC, around 1300–1500 mg kg −1 , are very close to the level determined in this study.…”
Section: Resluts and Discussionsupporting
confidence: 91%
“…Natural sources of antioxidants like fruits, vegetables and honey are currently sought‐after. Honey contains bioactive compounds such as phenols, flavonoids, carotenoids, vitamins, organic acids and other compounds, which might work synergistically to provide a positive antioxidant effect (Johnston et al , ; Gül & Pehlivan, ). As antioxidants, the aforementioned bioactive compounds could work through a myriad of mechanisms including donation of hydrogen atoms, scavenging for free radicals, quenching singlet oxygen, acting as substrates for some radicals and chelation of metal ions (Al‐Waili & Boni, ; Küçük et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the light‐colored honey such as rhododendron honey, oak, and chestnut honeys are known as dark‐colored honeys which generally demonstrate higher bioactivity effect (Gül & Pehlivan, ). The antioxidant investigation and physicochemical determination of some honey types collected from Anatolia showed that chestnut and heterofloral honeys were higher antioxidant values than rhododendron honey (Küçük et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The essence of the explanation, the differences or/and similarities of phenolic compounds in same type honeys were related to some parameters such as plant flora, pollen frequency, geographical area, climatic conditions, and collection year (Gül & Pehlivan, ).…”
Section: Discussionmentioning
confidence: 99%